Generalized granuloma annulare, perforating type in a scar in a patient with diabetes mellitus type 2 - Maciejowska, Judyta; Pasternak, Katarzyna; Leśniak, Małgorzata; Jaworek, Andrzej; Dyduch, Grzegorz; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Granuloma annulare is a chronic, benign, inflammatory skin disorder of an unknown etiology. The relationship between granuloma annulare and both types of diabetes mellitus is still controversial. In the PubMed database from the last 5 years there is one case report of a patient with diagnosed perforating type of granuloma annulare and 2 cases of coexistence of granuloma annulare and diabetes. Objective . Presentation of coexistence of perforating generalized granuloma annulare in the scar after cholecystectomy and diabetes mellitus type 2. Case report. A 63-year-old patient with a 3-year history of skin lesions and diabetes mellitus type 2 was admitted for detailed diagnostics and treatment. Dermatologic examination revealed disseminated polycyclic erythematous, infiltrative plaques arranged in an annular fashion. In the scar after cholecystectomy there were erythematous, infiltrative lesions with some sores. Similar lesions with numerous spot erosions covered by scab were found in the scar from a drain. The diagnosis was confirmed by histopathological examination. Intensive antidiabetic treatment has been introduced in order to normalize glucose level. In the course of applied therapy the normalization of blood glucose level and the partial remission of skin lesions have been observed. Conclusions . Detailed diagnostic tests to detect diabetes should be a mandatory element of medical procedures in every patient with recognized granuloma annulare.